Analisis Pengaruh Penghindaran Pajak, Profitabilitas dan Good Corporate Governance terhadap Nilai Perusahaan - Rhoudhoquth Salsabila; Nyimas Wardatul Afiqoh (STIE AMKOP, 2023)
This study aims to test and analyze the effect of tax avoidance, profitability and good corporate governance proxied by the board of directors, independent board of commissioners and audit committee on company value. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021. The samples in this study were obtained by purposive sampling techniques and based on predetermined criteria, a sample of 77 companies was obtained. This type of research is quantitative research with secondary data types. The analysis method used is multiple linear regression analysis with SPSS application tools. The results of the research analysis prove that tax avoidance and good corporate governance proxied by the board of directors, independent board of commissioners and audit committee have no influence significant to the value of the company while profitability has a significant effect on the value of the company. Keywords: Tax Avoidance, Profitability, Good Corporate Governance, Corporate Value.